Analysis of Short and Long Serves on the Effectiveness of Rallies and Point Acquisition in Badminton Athletes - Agan Fadhilah Mursyid; Mugiyo Hartono (Journal of Physical Education Health and Sport, 2026)
One of the basic techniques in badminton is serving, which is an important shooting at the beginning of a rally and maintains the pattern or while determining tempo and opportunities to control the game. The purpose of this study is to analyze the difference in effect between short serve and long serve on the effectiveness of rallies and point acquisition in 2025 Semarang Regency Championship. For the purpose of this study, a quantitative approach with a non-experimental observational comparative design was used. The research sample was 14 athletes in the Men's Beginner Singles (TPA-UTAMA) category, using a total sampling technique. Data were collected through systematic observation and video documentation of the matches. Data were analyzed using descriptive statistics, normality test, homogeneity test, and Paired Sample t-Test hypothesis test by using SPSS 26 software. The results: Short serve 51.63±20.60 Long serve 48.36±20.60 The average point and the average score of 53.06±8.49 were the same for both methods of acquiring points by rallying from attackers The normality test results revealed that all variables were normally distributed (p > 0.05) and the homogeneity test showed that there was heteroskedasticity between the variances (p 0.05). Such results suggest that both serve methods contribute relatively evenly to the success of rallies and point scoring. And at the regional training level, a match's success is based more on how solid the overall game is than what type of serve is being used. Real match data allow to evaluate these parameters and build a more complete training program.